The environmental impact of artificial intelligence (Revista ESASP - Revista Científica Virtual da Escola Superior de Advocacia da OAB/SP, 2025)
It reveals the substantial environmental costs of artificial intelligence, demystifying its apparent immateriality and demonstrating the need to rethink technological development through the lens of sustainability.(Received: September 2025 | Accepted: November 2025)
Keywords: Artificial Intelligence; Environmental Impact; Digital Technology; Sustainability; Energy Consumption